Antimicrobial and antibiofilm effect of silver nanoparticles on clinical isolates of multidrug resistant Klebsiella Pneumoniae - Eman Elsaid; Ola Ahmed; Abdullah Abdo; Shimaa Abdel Salam (Microbes and Infectious Diseases, 2023)
Background:  Multidrug-resistant (MDR) Klebsiella pneumoniae (K. pneumoniae) causes life threatening infections. Pharmaceutical nanotechnology is anticipated to produce new therapeutic products for biomedical uses. One of these compounds, silver nanoparticles (AgNPs), is with promising antibacterial and anti-biofilm characteristics. Aim of the work: To evaluate the anti-microbial and anti-biofilm activities of AgNPs against MDR K. pneumoniae clinical isolates in Ain-Shams university hospitals. Methodology: The study was conducted on fifty MDR K. pneumoniae. The isolates were retrieved from Ain Shams university Microbiology laboratory. The biofilm-forming activity was tested by a microtiter plate based on crystal violet staining, the AgNPs were synthesized biologically and characterized by different methods. The antibacterial and antibiofilm activities of biosynthesized AgNPs were investigated against selected strains using standard methods. Results: The results revealed that all isolates were resistant to tested antibiotics and biofilm-forming ability was detected in 28/50 (56%) isolates. The antibacterial activities of AgNPs showed that all isolates were susceptible to AgNPs with Minimal Inhibitory Concentration (MIC) ranging from 15.625 μg /ml to 125 μg /ml. Also, AgNPs significantly reduced the biofilm formation as 26/28 of isolates became non-biofilm producers (0) and 2/28 became weak.  Silver nanoparticles showed minimal cytotoxic concentration (conc.) up to 100 percent and 99.42 percent viability on normal human lung fibroblast cells (MRC-5) cell lines treated with AgNPs at conc. of 2 μg/ml and 3.9 μg/ml respectively. Conclusion: Multi drug resistant K. pneumoniae is a rising problem and the rate of biofilm formation in these isolates is high.  Silver nanoparticles exhibit good antibacterial and antibiofilm activity against them.